TB18 titanium alloy standard substance and preparation method thereof
By preparing TB18 titanium alloy chip-like standard substances, the problem of lack of TB18 titanium alloy standard samples in the prior art is solved, and the quality control of titanium alloy component detection is improved and market demand is met.
Patent Information
- Application Number
- CN202411829652.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The lack of standard samples of TB18 titanium alloy in the prior art leads to limitations in the quality control of titanium alloy components detection, and it is impossible to effectively detect the distribution of niobium elements in the 0.5% to 1.5% content and chromium elements in the 4.5% to 6.5% content.
A standard substance of TB18 titanium alloy chips and its preparation method are provided. By selecting 0-level sponge titanium and intermediate alloy as raw materials, using vacuum plasma welding technology to prepare consumable electrodes, four smelting and homogenizing heat treatment, and finally, high uniformity titanium alloy standard substance is prepared by forging and milling chips.
It fills the gap in domestic TB18 titanium alloy standard substances, improves the composition uniformity and accuracy of titanium alloy ingots, and meets the market's demand for TB18 titanium alloy chemical standard substances.
Smart Images

Figure CN119843102A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloy materials and relates to a TB18 titanium alloy standard substance and a preparation method thereof. Background Art
[0002] As an advanced aviation material, titanium alloy has become one of the main structural materials for contemporary aircraft and engines due to its low density, excellent corrosion resistance, higher specific strength, good high temperature performance and fatigue resistance. In foreign advanced aviation engines, the amount of titanium alloy used has accounted for 25% to 40% of the total weight of the engine. The number of applications and the level of use of titanium alloys have become one of the symbols for measuring the level of a country's aviation industry. With the continuous development of domestic aircraft and engines, the amount of titanium and titanium alloys used has also increased year by year, and the use of standard samples of titanium and titanium alloys will also gradually increase. As an excellent aviation material, TB18 titanium alloy is an ultra-high strength and toughness titanium alloy for aviation structures with good development prospects because of its high specific strength, deep hardenability, good corrosion resistance and excellent strength-plasticity-toughness matching that can be obtained through heat treatment strengthening.
[0003] Due to the difficulty in developing TB18 titanium alloy standard materials, after investigation, it was found that there are no standard samples of this alloy grade at home and abroad at this stage. Although imported standard samples can cover multiple detection elements, the content range is limited, and there are still limitations in the quality control of the detection process of diversified titanium alloy components in my country. With the continuous improvement of the requirements for the uniformity of material composition and the accuracy of detection, it has formed a huge contradiction with the lack of high-level TB18 chemical standards. Therefore, the development of TB18 titanium alloy chemical standard materials can not only meet market demand, but also fill the gap in my country's standard system.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to overcome the disadvantages of the prior art and provide a TB18 titanium alloy chip-like standard material and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides a TB18 titanium alloy chip-shaped standard material, wherein the content of each main element is in the range of: Al: 3.0%-5.0%, Mo: 5.05%-5.45%, V: 4.0%-5.8%, Cr: 4.5%-6.5%, Nb: 0.5%-1.5%, Fe: 0.03%-1.0%, and the rest is Ti and inevitable impurity elements, and the sum of the weight percentages of each element is 100%.
[0008] In addition, the present invention also provides a method for preparing a TB18 titanium alloy chip-shaped standard material, comprising the following steps:
[0009] Step 1, ingredients: select grade 0 titanium sponge, molybdenum-vanadium-aluminum-chromium master alloy, molybdenum-aluminum master alloy, vanadium-aluminum master alloy, niobium-titanium master alloy and aluminum beans as raw materials, calculate the ingredients according to the requirements of the content of each element of TB18 titanium alloy standard material, and weigh the raw materials of each component for use;
[0010] Step 2, preparation of consumable electrode: firstly, the raw materials of each component are mixed evenly and then pressed into electrode blocks of corresponding specifications, then the pressed electrode blocks are placed into a vacuum plasma welding box, and finally the consumable electrode is obtained by non-tungsten electrode argon shielded plasma welding process;
[0011] Step 3, smelting: smelting the consumable electrode at least four times to obtain a TB18 titanium alloy ingot;
[0012] Step 4, homogenization heat treatment: performing homogenization heat treatment on the TB18 titanium alloy ingot, so that the unbalanced eutectic structure in the TB18 titanium alloy ingot is evenly distributed in the matrix, and the composition and structure are more uniform;
[0013] Step 5, forging: forging the TB18 titanium alloy ingot after homogenization heat treatment to obtain a forged rod blank of a high-homogeneity titanium alloy standard material;
[0014] Step 6: Process the forged rod blank of the high uniformity titanium alloy standard material to complete the preparation of the TB18 titanium alloy standard material.
[0015] Specifically, in step 1, the use of grade 0 titanium sponge can reduce the impurity content in the titanium sponge and improve the purity of the ingot; the particle size diameter of the grade 0 titanium sponge is 0.83mm to 12.7mm, which can make the distribution of the titanium sponge more uniform; at the same time, niobium element is added in the form of niobium aluminum alloy in the form of chips because of its high melting point and easy to produce unmelted blocks; molybdenum and chromium elements are added in the form of quaternary alloy, which significantly reduces the melting point of the intermediate alloy.
[0016] Specifically, in step 2, in order to make the chemical composition more uniform, after the raw materials of each component are weighed, they are stirred and mixed by a mixing system, and the stirring time is not less than 30 seconds to ensure that the raw materials of each component are fully mixed; the mixed raw materials of each component are pressed into electrode blocks of corresponding specifications by a hydraulic press, and the pressing strength is 20MPa to 50MPa; the pressed electrode blocks are placed in a vacuum plasma welding box, and the pre-vacuum degree of the vacuum plasma welding box is less than 20Pa to prevent the consumable electrode from oxidizing, and the consumable electrode is prepared by a non-tungsten electrode argon shielded plasma welding process. In addition, the consumable electrode is inspected after welding to prevent the block from falling off during the smelting process and to ensure that there are no through cracks.
[0017] Specifically, in the smelting method in step 3, the first smelting and the last smelting are both carried out by vacuum consumable arc furnace smelting.
[0018] Further, step 3 includes three vacuum consumable arc furnace smeltings and one vacuum suspension smelting furnace smelting. The present invention defines that the first smelting and the last smelting are both smelted in a vacuum consumable arc furnace, wherein the second smelting is smelted in a vacuum consumable arc furnace, and the third smelting is smelted in a vacuum suspension smelting furnace; the smelting process parameters are as follows:
[0019] For the first smelting, the consumable electrode is placed in a vacuum consumable electrode arc furnace for the first smelting to obtain an ingot; the process parameters for the first smelting are: vacuum degree is less than 0.1Pa, arc stabilization current is 2A-10A, smelting current is set to 10KA-15KA, voltage is set to 30V-35V, and cooling time after smelting is greater than 4h.
[0020] In the second smelting, the primary ingot is machined to remove the flash at the head of the primary ingot, and after the head and tail are swapped, it is placed in a vacuum consumable electrode arc furnace for a second smelting to obtain a secondary ingot; the process parameters of the second smelting are: vacuum degree is less than 0.1Pa, arc stabilization current is set to 2A~8A, smelting current is set to 12KA~20KA, voltage is set to 30V~35V, and cooling time after smelting is greater than 4h.
[0021] In the third smelting, the secondary ingot obtained in the previous step is machined to remove the flash at the head of the secondary ingot, and the head and tail are swapped and placed in a vacuum suspension smelting furnace for suspension smelting to obtain a tertiary ingot; the process parameters of the third smelting are as follows: the smelting furnace chamber and the casting chamber are repeatedly evacuated at least 3 times: among which, the vacuum degree of the smelting furnace chamber must be less than 0.04Pa, and the vacuum degree of the casting chamber must be less than 0.5Pa; after turning on the induction heating power supply, the graphite mold is heated to 1000℃~1200℃ at a rate of 20℃ / min~30℃ / min and kept warm for 1h~2h; the smelting power is gradually increased to 500kW~900kW at a rate of 40kW / min~50kW / min, and the furnace temperature reaches 1300℃~1600℃ and is maintained for 30min~60min; after the smelting is completed, the alloy is cast into a graphite mold of specified specifications through a funnel at a speed of 5kg / s~10kg / s.
[0022] Fourth smelting: the tertiary ingots are machined to remove the flash at the heads of the tertiary ingots, and after the heads and tails are swapped, they are placed in a vacuum consumable electrode arc furnace for the fourth smelting to obtain TB18 titanium alloy ingots; the process parameters of the fourth smelting are: the vacuum degree is less than 0.1Pa, the arc stabilizing current is set to 2A~8A, the smelting current is set to 10KA~18KA, the voltage is set to 25V~30V, and the cooling time after smelting is greater than 4h.
[0023] In the above four smelting processes, the second smelting can also be smelting in a vacuum suspension smelting furnace, and the third smelting is smelting in a vacuum consumable arc furnace. The applicant needs to explain that, in principle, vacuum suspension furnace smelting can occur in any other smelting process except the first smelting and the last smelting. Combining vacuum consumable electrode arc furnace smelting can obtain materials with very uniform and accurate composition, and the vacuum suspension furnace smelting process can prepare materials with very high purity, which greatly improves the composition accuracy of titanium alloy ingot smelting.
[0024] Specifically, the heating temperature of the homogenization heat treatment in step 4 is 900° C. to 1100° C., and the temperature is kept for 10 h to 15 h.
[0025] Specifically, in step 5, the forging temperature is 800°C to 1200°C, and the forging temperature is reduced to below the phase transformation point in each fire, the forging ratio of each fire is 1.0 to 2.0, and 3 to 6 fires of forging are performed in total.
[0026] Specifically, in step 6, the preparation of chip-like TB18 titanium alloy standard material: first use a lathe to remove the oxide scale on the surface of the titanium alloy rod blank, and then use a milling machine to mill the chips, and finally obtain a chip-like TB18 titanium alloy standard material with a thickness of 0.2mm~0.5mm and a length of 1mm~3mm for inductively coupled plasma emission spectrometer testing.
[0027] Furthermore, the milling machine is equipped with a milling cutter made of YG8 material, with a milling cutter blade of 2 mm and a groove of 1 mm; the milling machine parameters are set as: chip speed 95 r / min, feed rate 76 mm / r, and feed depth 1.2 mm / time.
[0028] Specifically, in step 6, the block TB18 titanium alloy standard material is prepared by using a lathe to process the rod blank to Φ38mm×25mm for testing by a photoelectric direct reading spectrometer.
[0029] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0030] 1) The TB18 titanium alloy standard material provided by the present invention effectively fills the gap in domestic standard materials, solves the problem that there is no TB18 grade in the existing titanium alloy standard materials, and there are no effective distribution points in the titanium alloy standard samples for niobium elements in the content range of 0.5% to 1.5% and chromium elements in the content range of 4.5% to 6.5%, making it impossible to effectively detect alloy elements.
[0031] 2) The present invention provides an advanced method for melting titanium alloy ingots with high uniformity, which combines the vacuum consumable electrode arc furnace melting to obtain materials with very uniform and accurate composition, and the vacuum suspension melting to produce materials with very high purity, thereby greatly improving the uniformity and composition accuracy of titanium alloy ingot melting. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.
[0033] Figure 1 A physical state diagram of an ingot (without peeling) after four smeltings obtained in the preparation process of the preparation method provided in Example 1 of the present invention;
[0034] Figure 2 A physical picture of a forged rod blank obtained during the preparation process of the preparation method provided in Example 1 of the present invention;
[0035] Figure 3 A process diagram of the chip samples being screened, mixed, cleaned, and bottled during the chip preparation process provided in the preparation methods of Examples 1 to 4 of the present invention;
[0036] Figure 4 The present invention provides a flow chart of a method for preparing a TB18 titanium alloy standard material. DETAILED DESCRIPTION
[0037] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.
[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0039] Example 1
[0040] This embodiment provides a TB18 titanium alloy standard material, in which the content of each main element ranges as follows: Al: 3.0%, Mo: 5.05%, V: 4.0%, Cr: 4.5%, Nb: 0.5%, Fe: 0.03%, and the rest are Ti and unavoidable impurity elements, and the sum of the weight percentages of each element is 100%.
[0041] The flowchart of the preparation method of the standard substance is shown in Figure 4 , specifically including the following steps:
[0042] Step 1, ingredients: select grade 0 titanium sponge, molybdenum-vanadium-aluminum-chromium master alloy, molybdenum-aluminum master alloy, vanadium-aluminum master alloy, niobium-titanium master alloy and aluminum beans as raw materials, calculate the ingredients according to the requirements of the content of each element of TB18 titanium alloy standard material, and weigh the raw materials of each component for use;
[0043] Specifically, in step 1, the use of grade 0 titanium sponge can reduce the impurity content in the titanium sponge and improve the purity of the ingot; the particle size diameter of the grade 0 titanium sponge is 0.83mm to 12.7mm, which can make the distribution of the titanium sponge more uniform; at the same time, niobium element is added in the form of niobium aluminum alloy in the form of chips because of its high melting point and easy to produce unmelted blocks; molybdenum and chromium elements are added in the form of quaternary alloy, which significantly reduces the melting point of the intermediate alloy.
[0044] Step 2, preparation of consumable electrode: firstly, the raw materials of each component are mixed evenly and then pressed into electrode blocks of corresponding specifications, then the pressed electrode blocks are placed into a vacuum plasma welding box, and finally the consumable electrode is obtained by non-tungsten electrode argon shielded plasma welding process;
[0045] Specifically, in step 2, in order to make the chemical composition more uniform, after the raw materials of each component are weighed, the raw materials of each component are stirred and mixed by a mixing system for 40 seconds to ensure that the raw materials of each component are fully mixed; the mixed raw materials of each component are pressed into electrode blocks of corresponding specifications by a hydraulic press, and the pressing strength is 20MPa; the pressed electrode blocks are placed in a vacuum plasma welding box. To prevent the oxidation of the consumable electrode, the pre-vacuum degree of the vacuum plasma welding box is less than 20Pa, and the consumable electrode is prepared by a non-tungsten electrode argon shielded plasma welding process. In addition, the consumable electrode is inspected after welding to prevent the block from falling off during the smelting process and to ensure that there are no through cracks.
[0046] Step 3: The four smelting methods and related process parameters are as follows:
[0047] First smelting: Put the consumable electrode into a vacuum consumable electrode arc furnace for the first smelting to obtain a primary ingot; the process parameters for the first smelting are: vacuum degree is less than 0.1pa, arc stabilization current is set to 2A~10A, smelting current is set to 10KA~15KA, and voltage is set to 30V~35V; it should be emphasized that: suitable vacuum degree can ensure the removal of gas elements in the raw materials, such as Cl element, and suitable stirring intensity can make the molten pool move fully to ensure the uniformity of macroscopic composition; the current needs to be reduced before the end of smelting to reduce the molten pool depth at the head of the primary ingot and reduce head segregation; after the smelting is completed, the primary ingot can be fully cooled to ensure that the surface of the primary ingot is silvery white and shiny, without yellowing, purple and other oxidation phenomena.
[0048] Second smelting: machining the primary ingot to remove the flash at the head of the primary ingot, swapping the head and tail and placing the ingot in a vacuum consumable electrode arc furnace for a second smelting to obtain a secondary ingot; the process parameters for the second smelting are: vacuum degree less than 0.1Pa, arc stabilization current set to 5A-15A, smelting current set to 12KA-20KA, voltage set to 30V-35V, cooling time after smelting for 5h; since the gas impurities in the primary smelting have been basically removed, the smelting current can be appropriately increased in the secondary smelting, further increasing the stirring intensity of the molten pool and improving the uniformity of the macroscopic composition of the ingot.
[0049] The third smelting: the secondary ingot is machined to remove the flash at the head of the secondary ingot, and the head and tail are swapped and placed in a vacuum suspension smelting furnace for suspension smelting to obtain a tertiary ingot; the process parameters of the third smelting are: the smelting furnace chamber and the casting chamber are repeatedly evacuated 3 times: wherein, the vacuum degree of the smelting furnace chamber needs to be less than 0.04Pa, and the vacuum degree of the casting chamber needs to be less than 0.5Pa; after turning on the induction heating power supply, the graphite mold is heated to 1000℃ at a rate of 20℃ / min and kept warm for 1h; the smelting power is gradually increased to 500kW at a rate of 40kW / min, and then the furnace temperature reaches 1300℃ and is maintained for 30min; after the smelting is completed, the alloy is cast into a graphite mold of specified specifications through a funnel at a speed of 5kg / s.
[0050] Fourth smelting: The three ingots are machined to remove the flash at the head of the three ingots, and the heads and tails are replaced and placed in a vacuum consumable electrode arc furnace for the fourth smelting to obtain TB18 titanium alloy ingots. The actual state of the unpeeled ingot is shown in the figure. Figure 1 As shown; the process parameters of the fourth smelting are: vacuum degree is less than 0.1Pa, arc stabilization current is set to 2A ~ 8A, melting current is set to 10KA ~ 18KA, voltage is set to 25V ~ 30V, and cooling time after melting is 4h.
[0051] Step 4, homogenization heat treatment: the TB18 titanium alloy ingot is subjected to homogenization heat treatment at a heating temperature of 900° C. for 10 hours, so that the unbalanced eutectic structure in the TB18 titanium alloy ingot is evenly distributed in the matrix, and the composition and structure are more uniform.
[0052] Step 5, forging: forging the TB18 titanium alloy ingot after homogenization heat treatment to obtain a high uniformity titanium alloy standard material forging bar blank, such as Figure 2 As shown; the forging temperature is 800°C, and the forging temperature is reduced to below the phase transformation point in each fire, the forging ratio of each fire is 1.0, and 3 fire forgings are performed in total.
[0053] Step 6, preparation of chip-like TB18 titanium alloy standard material: first use a lathe to remove the oxide scale on the surface of the titanium alloy bar blank, and then use a milling machine to mill the chips, equipped with a YG8 milling cutter with a 2mm milling cutter blade and a 1mm groove. The milling machine parameters are set to: chip speed 95r / min, feed rate 76mm / r, feed depth 1.2mm / time, and finally prepare chip-like TB18 titanium alloy standard material with a thickness of 0.2mm~0.5mm and a length of 1~3mm. The specific packaging process is as follows Figure 3 As shown, it can be used for inductively coupled plasma optical emission spectrometer testing.
[0054] Alternatively, in step 6, the preparation of block TB18 titanium alloy standard material: the rod blank is processed into Φ38mm×25mm by a lathe for testing by a photoelectric direct reading spectrometer.
[0055] Example 2
[0056] This embodiment provides another TB18 titanium alloy chip-like standard material, in which the content of each main element ranges as follows: Al: 4.0%, Mo: 5.25%, V: 5.0%, Cr: 5.5%, Nb: 1.0%, Fe: 0.06%, and the rest are Ti and unavoidable impurity elements, and the sum of the weight percentages of each element is 100%.
[0057] The flowchart of the preparation method of the standard substance is shown in Figure 4 , specifically including the following steps:
[0058] Step 1, ingredients: select grade 0 titanium sponge, molybdenum-vanadium-aluminum-chromium master alloy, molybdenum-aluminum master alloy, vanadium-aluminum master alloy, niobium-titanium master alloy and aluminum beans as raw materials, calculate the ingredients according to the requirements of the content of each element of TB18 titanium alloy standard material, and weigh the raw materials of each component for use;
[0059] Specifically, in step 1, the use of grade 0 titanium sponge can reduce the impurity content in the titanium sponge and improve the purity of the ingot; the particle size diameter of the grade 0 titanium sponge is 0.83mm to 12.7mm, which can make the distribution of the titanium sponge more uniform; at the same time, niobium element is added in the form of niobium aluminum alloy in the form of chips because of its high melting point and easy to produce unmelted blocks; molybdenum and chromium elements are added in the form of quaternary alloy, which significantly reduces the melting point of the intermediate alloy.
[0060] Step 2, preparation of consumable electrode: firstly, the raw materials of each component are mixed evenly and then pressed into electrode blocks of corresponding specifications, then the pressed electrode blocks are placed into a vacuum plasma welding box, and finally the consumable electrode is obtained by non-tungsten electrode argon shielded plasma welding process;
[0061] Specifically, in step 2, in order to make the chemical composition more uniform, after the raw materials of each component are weighed, the raw materials of each component are stirred and mixed by a mixing system for 50 seconds to ensure that the raw materials of each component are fully mixed; the mixed raw materials of each component are pressed into electrode blocks of corresponding specifications by a hydraulic press, and the pressing strength is 50MPa; the pressed electrode blocks are placed in a vacuum plasma welding box. To prevent the oxidation of the consumable electrode, the pre-vacuum degree of the vacuum plasma welding box is less than 20Pa, and the consumable electrode is prepared by a non-tungsten electrode argon shielded plasma welding process. In addition, the consumable electrode is inspected after welding to prevent the block from falling off during the smelting process and to ensure that there are no through cracks.
[0062] Step 3: The four smelting methods and related process parameters are as follows:
[0063] First smelting: Put the consumable electrode into a vacuum consumable electrode arc furnace for the first smelting to obtain a primary ingot; the process parameters for the first smelting are: vacuum degree is less than 0.1pa, arc stabilization current is set to 2A~10A, smelting current is set to 10KA~15KA, and voltage is set to 30V~35V; it should be emphasized that: suitable vacuum degree can ensure the removal of gas elements in the raw materials, such as Cl element, and suitable stirring intensity can make the molten pool fully move to ensure the uniformity of macroscopic composition; the current needs to be reduced before the end of smelting to reduce the molten pool depth at the head of the primary ingot and reduce head segregation; after the smelting is completed, the primary ingot is fully cooled to ensure that the surface of the primary ingot is silvery white and shiny, without yellowing, purple and other oxidation phenomena.
[0064] Second smelting: the primary ingot is machined to remove the flash at the head of the primary ingot, and the head and tail are swapped and placed in a vacuum suspension smelting furnace for suspension smelting to obtain a secondary ingot; the process parameters of the second smelting are as follows: the smelting furnace chamber and the casting chamber are repeatedly evacuated at least 3 times: wherein the vacuum degree of the smelting furnace chamber must be less than 0.04Pa, and the vacuum degree of the casting chamber must be less than 0.5Pa; after turning on the induction heating power supply, the graphite mold is heated to 1200℃ at a rate of 30℃ / min and kept warm for 2h; the smelting power is gradually increased to 900kW at a rate of 50kW / min, and then the furnace temperature reaches 1600℃ and is maintained for 60min; after the smelting is completed, the alloy is cast into a graphite mold of specified specifications through a funnel at a speed of 10kg / s.
[0065] The third smelting: the secondary ingot is machined to remove the flash at the head of the secondary ingot, and the head and tail are swapped before being placed in a vacuum consumable electrode arc furnace for the third smelting to obtain a tertiary ingot; the process parameters for the third smelting are: the vacuum degree is less than 0.1Pa, the arc stabilization current is set to 5A~15A, the smelting current is set to 12KA~20KA, the voltage is set to 30V~35V, and the cooling time after smelting is 6h; since the gas impurities in the first smelting have been basically removed, the smelting current can be appropriately increased for the third smelting, the stirring intensity of the molten pool can be further increased, and the uniformity of the macroscopic composition of the tertiary ingot is improved.
[0066] Fourth smelting: the tertiary ingots are machined to remove the flash at the heads of the tertiary ingots, and after the heads and tails are swapped, they are placed in a vacuum consumable electrode arc furnace for the fourth smelting to obtain TB18 titanium alloy ingots; the process parameters of the fourth smelting are: vacuum degree is less than 0.1Pa, arc stabilization current is set to 2A~8A, smelting current is set to 10KA~18KA, voltage is set to 25V~30V, and cooling time after smelting is 5h.
[0067] Step 4, homogenization heat treatment: the TB18 titanium alloy ingot is subjected to homogenization heat treatment at a heating temperature of 1100° C. and kept warm for 15 hours, so that the unbalanced eutectic structure in the TB18 titanium alloy ingot is evenly distributed in the matrix and the composition and structure are more uniform.
[0068] Step 5, forging: forging the TB18 titanium alloy ingot after homogenization heat treatment to obtain a high-uniformity titanium alloy standard material forging rod blank; the forging temperature is 1200°C, and the forging temperature is reduced to below the phase transformation point in each fire, the forging ratio of each fire is 2.0, and a total of 5 fires of forging are performed.
[0069] Step 6, preparation of chip-like TB18 titanium alloy standard material: first use a lathe to remove the oxide scale on the surface of the titanium alloy bar blank, and then use a milling machine to mill the chips, equipped with a YG8 milling cutter with a 2mm milling cutter blade and a 1mm groove. The milling machine parameters are set as follows: chip speed 95r / min, feed rate 76mm / r, feed depth 1.2mm / time, and finally prepare chip-like TB18 titanium alloy standard materials with a thickness of 0.2mm~0.5mm and a length of 1~3mm for inductively coupled plasma emission spectrometer testing.
[0070] Alternatively, in step 6, the preparation of block TB18 titanium alloy standard material: the rod blank is processed into Φ38mm×25mm by a lathe for testing by a photoelectric direct reading spectrometer.
[0071] Example 3
[0072] This embodiment provides another TB18 titanium alloy chip-like standard material, in which the content of each main element ranges as follows: Al: 5.0%, Mo: 5.45%, V: 5.8%, Cr: 6.5%, Nb: 1.5%, Fe: 1.0%, and the rest are Ti and unavoidable impurity elements, and the sum of the weight percentages of each element is 100%.
[0073] The flowchart of the preparation method of the standard substance is shown in Figure 4 , specifically including the following steps:
[0074] Step 1, ingredients: select grade 0 titanium sponge, molybdenum-vanadium-aluminum-chromium master alloy, molybdenum-aluminum master alloy, vanadium-aluminum master alloy, niobium-titanium master alloy and aluminum beans as raw materials, calculate the ingredients according to the requirements of the content of each element of TB18 titanium alloy standard material, and weigh the raw materials of each component for use;
[0075] Specifically, in step 1, the use of grade 0 titanium sponge can reduce the impurity content in the titanium sponge and improve the purity of the ingot; the particle size diameter of the grade 0 titanium sponge is 0.83mm to 12.7mm, which can make the distribution of the titanium sponge more uniform; at the same time, niobium element is added in the form of niobium aluminum alloy in the form of chips because of its high melting point and easy to produce unmelted blocks; molybdenum and chromium elements are added in the form of quaternary alloy, which significantly reduces the melting point of the intermediate alloy.
[0076] Step 2, consumable electrode preparation: firstly, the raw materials of each component are mixed evenly and then pressed into electrode blocks of corresponding specifications, then the pressed electrode blocks are placed into a vacuum plasma welding box, and finally the consumable electrode is obtained by non-tungsten electrode argon shielded plasma welding;
[0077] Specifically, in step 2, in order to make the chemical composition more uniform, after the raw materials of each component are weighed, the raw materials of each component are stirred and mixed by a mixing system for 50 seconds to ensure that the raw materials of each component are fully mixed; the mixed raw materials of each component are pressed into electrode blocks of corresponding specifications by a hydraulic press, and the pressing strength is 50MPa; the pressed electrode blocks are placed in a vacuum plasma welding box. To prevent the oxidation of the consumable electrode, the pre-vacuum degree of the vacuum plasma welding box is less than 20Pa, and the consumable electrode is prepared by non-tungsten electrode argon shielded plasma welding. Moreover, the consumable electrode is inspected after welding to prevent the block from falling off during the smelting process and to ensure that there are no through cracks.
[0078] Step 3: The four smelting methods and related process parameters are as follows:
[0079] First smelting: Put the consumable electrode into a vacuum consumable electrode arc furnace for the first smelting to obtain a primary ingot; the process parameters for the first smelting are: vacuum degree is less than 0.1pa, arc stabilization current is 2A~10A, smelting current is set to 10KA~15KA, and voltage is set to 30V~35V; it should be emphasized that: suitable vacuum degree can ensure the removal of gas elements in the raw materials, such as Cl element, and suitable stirring intensity can make the molten pool move fully to ensure the uniformity of macroscopic composition; the current needs to be reduced before the end of smelting to reduce the molten pool depth at the head of the primary ingot and reduce head segregation; after the smelting is completed, the primary ingot is fully cooled to ensure that the surface of the primary ingot is silvery white and shiny, without yellowing, purple and other oxidation phenomena.
[0080] Second smelting: the primary ingot is machined to remove the flash at the head of the primary ingot, and after the head and tail are swapped, it is placed in a vacuum suspension smelting furnace for suspension smelting to obtain a secondary ingot; the process parameters of the second smelting are as follows: the smelting furnace chamber and the casting chamber are repeatedly evacuated at least 3 times: wherein, the vacuum degree of the smelting furnace chamber must be less than 0.04Pa, and the vacuum degree of the casting chamber must be less than 0.5Pa; after turning on the induction heating power supply, the graphite mold is heated to 1200℃ at a rate of 25℃ / min and kept warm for 3h; the smelting power is gradually increased to 900kW at a rate of 45kW / min, and the furnace temperature is brought to 1600℃ and maintained for 30min; after the smelting is completed, the alloy is cast into a graphite mold of specified specifications through a funnel at a speed of 10kg / s.
[0081] The third smelting: the secondary ingot is machined to remove the flash at the head of the secondary ingot, and the head and tail are swapped before being placed in a vacuum consumable electrode arc furnace for the third smelting to obtain a tertiary ingot; the process parameters for the third smelting are: the vacuum degree is less than 0.1Pa, the arc stabilization current is set to 5A~15A, the smelting current is set to 12KA~20KA, the voltage is set to 30V~35V, and the cooling time after smelting is 5h; since the gas impurities in the first smelting have been basically removed, the smelting current can be appropriately increased for the third smelting, the stirring intensity of the molten pool is further increased, and the uniformity of the macroscopic composition of the ingot is improved.
[0082] Fourth smelting: the tertiary ingots are machined to remove the flash at the heads of the tertiary ingots, and after the heads and tails are swapped, they are placed in a vacuum consumable electrode arc furnace for the fourth smelting to obtain TB18 titanium alloy ingots; the process parameters of the fourth smelting are: the vacuum degree is less than 0.1Pa, the arc stabilizing current is set to 2A~8A, the smelting current is set to 10KA~18KA, the voltage is set to 25V~30V, and the cooling time after smelting is 4h.
[0083] Step 4, homogenization heat treatment: the TB18 titanium alloy ingot is subjected to homogenization heat treatment at a heating temperature of 1100° C. and kept warm for 15 hours, so that the unbalanced eutectic structure in the TB18 titanium alloy ingot is evenly distributed in the matrix and the composition and structure are more uniform.
[0084] Step 5, forging: forging the TB18 titanium alloy ingot after homogenization heat treatment to obtain a high-uniformity titanium alloy standard material forging rod blank; the forging temperature is 1100°C, and the forging temperature is reduced to below the phase transformation point in each fire, the forging ratio of each fire is 1.5, and a total of 6 fires of forging are performed.
[0085] Step 6, preparation of chip-like TB18 titanium alloy standard material: first use a lathe to remove the oxide scale on the surface of the titanium alloy bar blank, and then use a milling machine to mill the chips, equipped with a YG8 milling cutter with a 2mm milling cutter blade and a 1mm groove. The milling machine parameters are set as follows: chip speed 95r / min, feed rate 76mm / r, feed depth 1.2mm / time, and finally prepare chip-like TB18 titanium alloy standard materials with a thickness of 0.2mm~0.5mm and a length of 1~3mm for inductively coupled plasma emission spectrometer testing.
[0086] Alternatively, in step 6, the preparation of block TB18 titanium alloy standard material: the rod blank is processed into Φ38mm×25mm by a lathe for testing by a photoelectric direct reading spectrometer.
[0087] Example 4
[0088] This embodiment provides another TB18 titanium alloy chip-like standard material, in which the content of each main element ranges as follows: Al: 4.2%, Mo: 5.15%, V: 4.8%, Cr: 5.0%, Nb: 1.2%, Fe: 0.08%, and the rest are Ti and unavoidable impurity elements, and the sum of the weight percentages of each element is 100%.
[0089] The flowchart of the preparation method of the standard substance is shown in Figure 4 , specifically including the following steps:
[0090] Step 1, ingredients: select grade 0 titanium sponge, molybdenum-vanadium-aluminum-chromium master alloy, molybdenum-aluminum master alloy, vanadium-aluminum master alloy, niobium-titanium master alloy and aluminum beans as raw materials, calculate the ingredients according to the requirements of the content of each element of TB18 titanium alloy standard material, and weigh the raw materials of each component for use;
[0091] Specifically, in step 1, the use of grade 0 titanium sponge can reduce the impurity content in the titanium sponge and improve the purity of the ingot; the particle size diameter of the grade 0 titanium sponge is 0.83mm to 12.7mm, which can make the distribution of the titanium sponge more uniform; at the same time, niobium element is added in the form of niobium aluminum alloy in the form of chips because of its high melting point and easy to produce unmelted blocks; molybdenum and chromium elements are added in the form of quaternary alloy, which significantly reduces the melting point of the intermediate alloy.
[0092] Step 2, preparation of consumable electrode: firstly, the raw materials of each component are mixed evenly and then pressed into electrode blocks of corresponding specifications, then the pressed electrode blocks are placed into a vacuum plasma welding box, and finally the consumable electrode is obtained by non-tungsten electrode argon shielded plasma welding process;
[0093] Specifically, in step 2, in order to make the chemical composition more uniform, after the raw materials of each component are weighed, the raw materials of each component are stirred and mixed by a mixing system for 50 seconds to ensure that the raw materials of each component are fully mixed; the mixed raw materials of each component are pressed into electrode blocks of corresponding specifications by a hydraulic press, and the pressing strength is 50MPa; the pressed electrode blocks are placed in a vacuum plasma welding box. To prevent the oxidation of the consumable electrode, the pre-vacuum degree of the vacuum plasma welding box is less than 20Pa, and the consumable electrode is prepared by a non-tungsten electrode argon shielded plasma welding process. Moreover, the consumable electrode is inspected after welding to prevent the block from falling off during the smelting process and to ensure that there are no through cracks.
[0094] Step 3, five smeltings, the smelting method and related process parameters are as follows:
[0095] First smelting: Put the consumable electrode into a vacuum consumable electrode arc furnace for the first smelting to obtain a primary ingot; the process parameters for the first smelting are: vacuum degree is less than 0.1pa, arc stabilization current is set to 2A~10A, smelting current is set to 10KA~15KA, and voltage is set to 30V~35V; it should be emphasized that: suitable vacuum degree can ensure the removal of gas elements in the raw materials, such as Cl element, and suitable stirring intensity can make the molten pool move fully to ensure the uniformity of macroscopic composition; the current needs to be reduced before the end of smelting to reduce the molten pool depth at the head of the primary ingot and reduce head segregation; after the smelting is completed, the primary ingot can be fully cooled to ensure that the surface of the primary ingot is silvery white and shiny, without yellowing, purple and other oxidation phenomena.
[0096] Second smelting: machining the primary ingot to remove the flash at the head of the primary ingot, swapping the head and tail and placing the ingot in a vacuum consumable electrode arc furnace for a second smelting to obtain a secondary ingot; the process parameters for the second smelting are: vacuum degree less than 0.1Pa, arc stabilization current set to 5A-15A, smelting current set to 12KA-20KA, voltage set to 30V-35V, cooling time after smelting for 5h; since the gas impurities in the primary smelting have been basically removed, the smelting current can be appropriately increased in the secondary smelting, further increasing the stirring intensity of the molten pool and improving the uniformity of the macroscopic composition of the ingot.
[0097] The third smelting: the secondary ingot is machined to remove the flash at the head of the secondary ingot, and after the head and tail are swapped, it is placed in a vacuum consumable electrode arc furnace for the third smelting to obtain a tertiary ingot; the process parameters of the third smelting are: vacuum degree is less than 0.1Pa, arc stabilization current is set to 2A~8A, smelting current is set to 10KA~18KA, voltage is set to 25V~30V, and cooling time after smelting is 5h.
[0098] Fourth smelting: the three ingots are machined to remove the flash at the heads of the three ingots, and after the heads and tails are swapped, they are placed in a vacuum suspension smelting furnace for suspension smelting to obtain four ingots; the process parameters of the fourth smelting are as follows: the smelting furnace chamber and the casting chamber are repeatedly evacuated 3 times: wherein, the vacuum degree of the smelting furnace chamber must be less than 0.04Pa, and the vacuum degree of the casting chamber must be less than 0.5Pa; after turning on the induction heating power supply, the graphite mold is heated to 1200℃ at a rate of 25℃ / min and kept warm for 3h; the smelting power is gradually increased to 900kW at a rate of 40kW / min, and then the furnace temperature reaches 1300℃ and is maintained for 30min; after the smelting is completed, the alloy is cast into a graphite mold of specified specifications through a funnel at a speed of 10kg / s.
[0099] Fifth smelting: the four ingots are machined to remove the flash at the heads of the four ingots, and after the heads and tails are swapped, they are placed in a vacuum consumable electrode arc furnace for the fifth smelting to obtain TB18 titanium alloy ingots; the process parameters of the fifth smelting are: vacuum degree is less than 0.1Pa, arc stabilization current is set to 2A~8A, smelting current is set to 8KA~16KA, voltage is set to 25V~30V, and cooling time after smelting is 4h.
[0100] Step 4, homogenization heat treatment: the TB18 titanium alloy ingot is subjected to homogenization heat treatment at a heating temperature of 1100° C. and kept warm for 15 hours, so that the unbalanced eutectic structure in the TB18 titanium alloy ingot is evenly distributed in the matrix and the composition and structure are more uniform.
[0101] Step 5, forging: forging the TB18 titanium alloy ingot after homogenization heat treatment to obtain a high-uniformity titanium alloy standard material forging rod blank; the forging temperature is 1100°C, and the forging temperature is reduced to below the phase transformation point in each fire, the forging ratio of each fire is 1.5, and a total of 6 fires of forging are performed.
[0102] Step 6, preparation of chip-like TB18 titanium alloy standard material: first use a lathe to remove the oxide scale on the surface of the titanium alloy bar blank obtained in step 5, and then use a milling machine to mill the chips, equipped with a YG8 milling cutter with a 2mm milling cutter blade and a 1mm groove. The milling machine parameters are set as follows: chip speed 95r / min, feed rate 76mm / r, feed depth 1.2mm / time, and finally prepare chip-like TB18 titanium alloy standard materials with a thickness of 0.2mm~0.5mm and a length of 1~3mm for inductively coupled plasma emission spectrometer testing.
[0103] Alternatively, in step 6, the preparation of block TB18 titanium alloy standard material: the rod blank obtained in step 5 is processed into Φ38mm×25mm by a lathe for testing with a photoelectric direct reading spectrometer.
[0104] It should be noted that the uniformity of the standard substance is one of its most critical indicators. Therefore, it is necessary to perform a uniformity test on the standard substances prepared in the above Examples 1 to 4. The specific test process is as follows:
[0105] ① The initial inspection process of ingot uniformity is as follows:
[0106] After multiple smeltings are completed, the uniformity of element distribution is preliminarily judged by standard deviation. Three samples are taken at equal distances along the radial direction at the head, middle and tail ports for uniformity inspection. According to the provisions of YS / T 409 "Technical Specifications for Standard Samples", the standard deviation s of the test results is calculated and compared with the allowable difference Δ between laboratories. When 1.5s≤1 / 2Δ, the uniformity inspection is considered to be qualified. After detection and statistical calculation, the standard deviations of Al, Mo, Cr, V, Nb and Fe in the TB18 titanium alloy cylindrical ingot prepared in the above embodiment all meet the standard requirements.
[0107] ② Homogeneity test: According to GB / T 15000.3 "Guidelines for Standard Samples" and YS / T 409 "Technical Specifications for Standard Samples", the variance method is used to test the uniformity of the sample. The uniformity test includes two aspects: inter-unit uniformity and intra-unit uniformity; inter-unit uniformity reflects the difference in measurement results between each unit of the sample; intra-unit uniformity reflects the minimum sampling volume that can represent the entire unit, and it should be ensured that the typical sampling volume for daily analysis is larger than or at least equal to the minimum sampling volume.
[0108] In order to further verify the effectiveness of the technical solution provided by the present invention, a set of TB18 titanium alloy chip standard material uniformity test scheme is specially designed: 20 bottles with different numbers are randomly selected as uniformity research samples, and each bottle sample is analyzed and measured in parallel 3 times. The single-factor variance analysis method is adopted, that is, the calculation is performed by comparing the standard deviation between bottles (Samong) and the standard deviation within the bottle (Swithin).
[0109] To avoid fluctuations in the measurement process, the three measurements were performed in the following order (by unit number):
[0110] First measurement: 1-3-5-7-9-11-13-15-17-19-2-4-6-8-10-12-14-16-18-20
[0111] Second measurement: 20-19-18-17-16-15-14-13-12-11-10-9-8-7-6-5-4-3-2-1
[0112] The third measurement: 2-4-6-8-10-12-14-16-18-20-1-3-5-7-9-11-13-15-17-19
[0113] x 11 ,x 12 ,……x 1n ,average value
[0114] x 21 ,x 22 ,……x 2n ,average value
[0115] ………………, ………;
[0116] x m1 ,x m2 ,……x mn ,average value
[0117] Calculate the overall average
[0118] Calculate the sum of squared deviations within the bottle (where Q1 = MSwithin)
[0119] Calculate the sum of squares of deviations between bottles (where Q2 = MSamong)
[0120] Calculate the degree of freedom ν1=m-1;ν2=m(n-1)
[0121] Calculating Statistics
[0122] According to the significance level and degrees of freedom, F can be obtained from the F test critical value table. α Compare F and F α :
[0123] If F < F α , it is considered that there is no significant difference within and between groups and the sample is uniform.
[0124] If F ≥ F α , it is suspected that there are systematic errors between the groups and the samples are considered to be uneven.
[0125] From the results of the uniformity inspection F method in Table 1 below, it can be seen that the uniformity inspection of the TB18 titanium alloy chip standard material is qualified.
[0126] Table 1 Uniformity of TB18 titanium alloy chips
[0127]
[0128] In summary, the technical solution provided by the present invention, combined with the vacuum consumable electrode arc furnace smelting, can obtain materials with very uniform and accurate composition, and the vacuum suspension smelting can produce materials with very high purity, which greatly improves the uniformity and composition accuracy of titanium alloy ingot smelting, and can not only meet market demand, but also fill the gap in my country's TB18 standard sample system, and further contribute to the development of my country's aviation industry.
[0129] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0130] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A TB18 titanium alloy standard material, characterized in that: The content range of each element is: Al: 3.0% to 5.0%, Mo: 5.05% to 5.45%, V: 4.0% to 5.8%, Cr: 4.5% to 6.5%, Nb: 0.5% to 1.5%, Fe: 0.03% to 1.0%, and the rest are Ti and unavoidable impurity elements. The sum of the weight percentages of each element is 100%.
2. The method for preparing the TB18 titanium alloy standard material according to claim 1, characterized in that: The steps include: Step 1, ingredients: select grade 0 titanium sponge, molybdenum-vanadium-aluminum-chromium master alloy, molybdenum-aluminum master alloy, vanadium-aluminum master alloy, niobium-titanium master alloy and aluminum beans as raw materials, calculate the ingredients according to the requirements of the content of each element of TB18 titanium alloy standard material, and weigh the raw materials of each component for use; Step 2, preparation of consumable electrode: firstly, the raw materials of each component are mixed evenly and then pressed into electrode blocks of corresponding specifications, then the pressed electrode blocks are placed into a vacuum plasma welding box, and finally the consumable electrode is obtained by non-tungsten electrode argon shielded plasma welding process; Step 3, smelting: smelting the consumable electrode at least four times to obtain a TB18 titanium alloy ingot; Step 4, homogenization heat treatment: performing homogenization heat treatment on the TB18 titanium alloy ingot, so that the unbalanced eutectic structure in the TB18 titanium alloy ingot is evenly distributed in the matrix, and the composition and structure are more uniform; Step 5, forging: forging the TB18 titanium alloy ingot after homogenization heat treatment to obtain a forged rod blank of a high-homogeneity titanium alloy standard material; Step 6: Process the forged rod blank of the high uniformity titanium alloy standard material to complete the preparation of the TB18 titanium alloy standard material.
3. The method for preparing the TB18 titanium alloy standard material according to claim 2, characterized in that: In step 2, the various component raw materials are stirred and mixed by using a mixing system, and the stirring time is not less than 30 seconds; the mixed component raw materials are pressed into electrode blocks of corresponding specifications by using an oil press, and the pressing strength is 20MPa to 50MPa; the pre-vacuum degree of the vacuum plasma welding box is less than 20Pa.
4. The method for preparing the TB18 titanium alloy standard material according to claim 2, characterized in that: The smelting in step 3 includes: at least three times of smelting in a vacuum consumable arc furnace and one time of smelting in a vacuum suspension smelting furnace.
5. The method for preparing the TB18 titanium alloy standard material according to claim 4, characterized in that: In the smelting method in step 3, the first smelting and the last smelting are both carried out by vacuum consumable arc furnace smelting.
6. The method for preparing the TB18 titanium alloy standard material according to claim 4, characterized in that: The smelting process of the vacuum suspension furnace smelting is: The ingot obtained by the previous step of vacuum consumable arc furnace smelting is machined to remove the flash at the head, and after the head and tail are swapped, it is placed in a vacuum suspension smelting furnace for suspension smelting to obtain an intermediate ingot; wherein, the specific process of suspension smelting is: The melting furnace chamber and the casting chamber are repeatedly evacuated at least 3 times, and the vacuum degree of the melting furnace chamber is less than 0.04Pa, and the vacuum degree of the casting chamber is less than 0.5Pa; after turning on the induction heating power supply, the graphite mold is heated to 1000℃~1200℃ at a rate of 20℃ / min~30℃ / min and kept warm for 1h~3h; after increasing the melting power to 500kW~900kW at a rate of 40kW / min~50kW / min, the furnace temperature reaches 1300℃~1600℃ and is maintained for 30min~60min; after the melting is completed, the alloy is cast into a graphite mold of specified specifications through a funnel at a speed of 5kg / s~10kg / s.
7. The method for preparing the TB18 titanium alloy chips standard material according to claim 2, characterized in that: The heating temperature of the homogenization heat treatment in step 4 is 900° C. to 1100° C., and the temperature is kept for 10 h to 15 h.
8. The method for preparing the TB18 titanium alloy chips standard material according to claim 2, characterized in that: In step 5, the forging temperature is 800°C to 1200°C, and the forging temperature is reduced to below the phase transformation point in each fire, the forging ratio of each fire is 1.0 to 2.0, and 3 to 6 fires of forging are performed cumulatively.
9. The method for preparing the TB18 titanium alloy standard material according to claim 2, characterized in that: In step 6, the preparation of chip-like TB18 titanium alloy standard material: first use a lathe to remove the oxide scale on the surface of the rod blank, and then use a milling machine to mill the chips, and finally obtain a chip-like TB18 titanium alloy standard material with a thickness of 0.2mm~0.5mm and a length of 1mm~3mm for inductively coupled plasma emission spectrometer testing.
10. The method for preparing the TB18 titanium alloy standard material according to claim 2, characterized in that: In step 6, the block TB18 titanium alloy standard material is prepared by using a lathe to process the bar blank into Φ38mm×25mm for testing by a photoelectric direct reading spectrometer.
Citation Information
Patent Citations
Titanium alloys exhibiting resistance to impact or shock loading and method of making a part therefrom
CA2938089A1
WSTi45561 ultrahigh-strength titanium alloy and preparation method thereof
CN106119606A
Forging method of ultrahigh-toughness TB18 titanium alloy large-specification bar
CN114669700A
Preparation method of titanium-aluminum alloy, titanium-aluminum alloy and application
CN115896501A
High-performance titanium alloy composition for the manufacture of high-performance parts, particularly for the aerospace industry
FR2946363A1
Cited By
Method for testing chemical components in titanium alloy return scrap
CN120801287A